In vitro evaluation of marginal leakage at enamel and dentin treated by different laser densities - Aveiro, Rafael Zacatei; Yui, Karen Cristina Kazue; da Silva, Tânia Mara; Gonçalves, Lucélia Lemes; Esteves, Stella Renata Machado Silva; Gonçalves, Sérgio Eduardo de Paiva (Brazilian Dental Science, 2013)
Objectives: To evaluate “in vitro” the degree of marginal leakage in class V cavities irradiated with Nd:YAG laser onto enamel and dentin pretreated with bonding system (Single Bond, 3M ESPE) without light-curing. Material & Methods: Class V cavities were performed and standardized in 60 bovine incisors. After the acid etching, the teeth were divided into three groups: G1 – Application of bonding system, irradiation with Nd:YAG laser at 140 mJ/pulse without light-curing. G2 – Application of bonding system, irradiation with Nd:YAG laser at 200 mJ/pulse without light-curing. Group C - Application of bonding system and light-curing. Next, resin composite restorations were executed and thermocycled at alternated baths from 2 to 50 ºC (± 2 ºC), totalizing 500 cycles. To assess the microleakage, the teeth were submersed into 50% silver nitrate solution for 24 h, cut at 1 mm of thickness and analyzed through stereoscopy. The following leakage criterion scores were employed: 0 – none leakage; 1 – gingival or incisal wall; 2 – axial wall towards the pulp. Results : It was observed a high leakage frequency with score 1 among the experimental conditions. There was a higher predominance of score 2 leakage for control group at cementum. Concerning to enamel and cementum, Group C was similar to G1. By comparing control group with G2, and G1 with G2, it was verified statistically significant differences. Conclusion: The laser energy provided a reduction of the marginal leakage at enamel and dentin/ cementum; however, the energy density increase resulted in smaller marginal leakage at enamel and dentin/cementum. Keywords Nd-YAG Laser; Energy; Marginal leakage; Enamel; Dentin.